Effects of exogenous silicon on antioxidant capacities in sub-cellular fractions of asparagus bean seedlings under rust stress - DAI Dan-li; LIU Yong-hua; WU Xiao-hua; WANG Bao-gen; ZHU Zhu-jun (浙江大学学报. 农业与生命科学版)
The effects of exogenous silicon (Si) on antioxidant ability of two asparagus bean cultivars, ZN016 (highly resistant) and Zhijiang 282 (susceptible), were investigated at sub-cellular level (cytoplasm, chloroplast and mitochondria) under rust (Uromyces vignae) stress by substrate culture. The results indicate that application of exogenous Si significantly increased the activities of peroxidase (POD), ascorbate peroxidase (APX), catalase (CAT), and phenylalanine ammonia-lyase (PAL) in three sub-cellular fractions, and superoxide dismutase (SOD) activity of mitochondria for both cultivars, and the ascorbate acid (AsA) content in mitochondria of susceptible cultivar under rust stress. Consequently, the content of malonyldialdehyde (MDA) in cytoplasm and chloroplast of susceptible cultivar was significantly reduced by exogenous Si application under rust stress. These results above indicated that enhanced rust resistance of asparagus bean by exogenous Si application could increase their antioxidant capacities, which can quench reactive oxygen species more efficiently and maintain the integrity and biological function of cytoplasmic membrane and chloroplast membrane.